Kantorówka – Ośrodek Dokumentacji i Historii Regionu Muzeum Tadeusza Kantora - Walat, Irena (Instytut Sztuk Pięknych Uniwersytetu Rzeszowskiego, 2021)
The Kantorówka is as it were a living center of art and culture as well as a venue of many events integrating local communities. It is a treasury of the region culture, which attracts representatives of various creative groups and provides patronage for many cultural initiatives. A good illustration of the idea of a living museum were the Wielopole lessons, a reference to the lectures Tadeusz Kantor used to give to the students of Civica scuola d’arte drammatica di Milano at the Piccolo Teatro in Milan. The article describes an event initiated by Professor Marlena Makiel-Hędrzak.
The Wielopole lessons – the Tadeusz Kantor Museum – the Kantorówka Center for Documentation and History of the Region
Keywords: Lekcje wielopolskie; Kantorówka; The Wielopole lessons; the Kantorówka Center for Documentation and History of the Region